Antibiotic prescription behaviours in Lao People's Democratic Republic: a knowledge, attitude and practice survey - Fabrice Quet; Erika Vlieghe; Caroline Leyer; Yves Buisson; Paul N Newton; Philaysak Naphayvong; Valy Keoluangkhot; Monique Chomarat; Christophe Longuet; Nicolas Steenkeste; Jan Jacobs (The World Health Organization, 2015)
Objective To assess the antibiotic prescribing practices of doctors working in the Lao People's Democratic Republic and their knowledge of local antibiotic resistance patterns. Methods Doctors attending morning meetings in 25 public hospitals in four provinces were asked to complete a knowledge, attitude and practice survey. The questionnaire contained 43 multiple choice questions that the doctor answered at the time of the meeting. Findings The response rate was 83.4% (386/463). Two hundred and seventy doctors (59.8%) declared that they had insufficient information about antibiotics. Only 14.0% (54/386) recognized the possibility of cephalosporin cross-resistance in methicillin-resistant Staphylococcus aureus. Most participants had no information about local antibiotic resistance for Salmonella Typhi (211/385, 54.8%) and hospital-acquired pneumonia (253/384, 65.9%). Unnecessary antibiotic prescriptions were considered as harmless by 115 participants and 148 considered locally-available generic antibiotics to be of poor quality. Nearly three-quarters (280/386) of participants agreed that it was difficult to select the correct antibiotics. Most participants (373/386) welcomed educational programmes on antibiotic prescribing and 65.0% (249/383) preferred local over international antibiotic guidelines. Conclusion Doctors in the Lao People's Democratic Republic seem to favour antibiotic prescribing interventions. Health authorities should consider a capacity building programme that incorporates antibiotic prescribing and hospital infection control.